KOMUNIKASI POLITIK DAN KETERWAKILAN PEREMPUAN DALAM ARENA POLITIK - Susri Adeni; Machyudin Agung Harahap (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Women also become part of political activities. Unfortunately the representation of women has not been heard fully  in  the  public  space.  Many  women's  voices  have  not  been  conveyed.  This  article  describes  the  general picture  of  women  and  communication  in  the  political  arena  in  Indonesia.  Various  cases  from  various  studies show that communication and the role of women have not been significant in the political or legislative scene. Male  dominance  becomes  an  inseparable  part  because  of  the  strongly  embedded  culture  of  patriarchy  in Indonesia. But women do not stop fighting  for her voice. Dedication of women seen  in some areas by  making women  as  leaders.  It  shows  women's  progress  and  her  desire  to  move  forward  and  can  be  a  representation  of other women aspirations.Keywords: gender, political communication, women, politic